Henry and Beezus - Cleary, Beverly (Morrow junior books., 1952)
All Henry Huggins wants is his very own bicycle. But no matter how Henry tries to raise money for the bike of his dreams <U+2014> from selling bubble gum to delivering newspapers <U+2014> he always ends up with too much trouble and not enough money. But Henry's old friend Beezus has an idea that may turn Henry's worst trouble yet into a real business success!